Taxation, Labor Market Policy and High-Impact Entrepreneurship - Magnus Henrekson; Dan Johansson; Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2010)
Public policy affects the prevalence and performance of both productive and high-impact entrepreneurship. High-impact entrepreneurship prospers when knowledge is successfully generated and exploited in the economy. This process depends on complementary key ac-tors who use their competencies in what we denote a competence bloc. Although variations in economic contexts make prescribing a general panacea impossible, a number of relevant policy areas that affect key actors can be identified. In this paper this is done in the areas of tax policy and labor market policy. It is shown that high and/or distortive taxes and heavy labor market regulations impinge on the creation and functioning of competence blocs, thereby reducing high-impact entrepreneurship.
Keywords: H32; L25; L50; M13; O31; P14; 330; Entrepreneurship; Gazelles; High-growth firms; High-impact entrepreneurship Innovation; Institutions; Labor market policy; Tax policy; Entrepreneurship-Ansatz; Steuerpolitik; Unternehmensbesteuerung; Arbeitsmarktpolitik; Innovation